English Voiceless Stop Production of Javanese University Students in Yogyakarta - Hadari, Prahastuti Nastiti; Hardjanto, Tofan Dwi (Universitas Airlangga, 2024)
As a language taught almost everywhere in the world, English variations emerge, and they bring the characteristics of foreign learners’ first languages. Under this assumption, this study aimed to seek how Javanese phonological elements interfere with the production of English voiceless stops by Javanese students on a gender basis. Data in the form of sound recordings were collected from 36 students which consisted of 18 males and 18 females from two prominent universities in Yogyakarta. Using Praat, the voice onset time (VOT) of each sound was noted and processed using Microsoft Excel. The study result showed that based on the VOT means of 514 data, regardless of the position, both male and female students produced short-lagged /p/ and long-lagged /t/ and /k/, forming a pattern of /k/ > /t/ > /p/. Voiceless stops at the initial position have longer VOT than the medial position. Male students produced more phoneme shifts than female students. Male students seemed to be more Javanese-influenced in the way they produced more [ɽ], the retroflex version of t-flap [ɾ] as the English /t/ variation, at the medial position although they generally produced longer VOT than female students.